The siginificance of interreligious dialogue in building muslim-christian relations in Nigeria - Ashimi, Tijani Ahmad (Hamdard Foundation Press, Pakistan, 2014)
Nowadays and in this twenty first century, inter-religious dialogue is gaining momentum and importance at both national and international levels. Perhaps that is due to its role and goal in building bridges among different religious groups to promote respect, tolerance and peaceful living. Inter-religious dialogue is perhaps more important in Nigeria than anywhere else, on the grounds that Nigeria is the most populous country in the African continent, and it is moreover, a pluralistic and multi-religious society, which is mainly dominated by Islam and Christianity. Yet, in modern Nigeria, the relation between Muslims and their Christian compatriots is in continuous jeopardy (if not deteriorating). As such, the country has experienced various forms of religious violence between these two dominant religious groups, (Islam and Christianity) and these religions are even sometimes depicted as monolithic entities that confront each other in pitched battles. As a result of uncountable battles and confrontations, incalculable human losses and material damages are always attributed to religion. It is important to mention at this juncture, that no meaningful dialoguing has taken place in modern Nigeria. The only existing dialogues that are based on academic conferences and individual efforts appear to be ineffective. As far as peaceful coexistence is concerned, and given that religious tolerance is also important to it, there is no doubt that the best forum to promote Muslims-Christians relationship, and the right tool to tackle reoccurrence of religious conflict in the country is sound interreligious dialogue. Thus, this preliminary working paper will explore the meaning of inter-religious dialogue according to the Qur'ānic and Biblical perspectives. We will also discuss interreligious dialogue in Nigeria specifically. That will be followed by the causes behind the need for sound and effective interreligious dialogue in the Nigerian context. Lastly, the article will provide effective methods, guidelines and some action guides that can be utilized to achieve the goal of this forum in the Nigerian pluralistic society.